1997
DOI: 10.1111/j.1600-0749.1997.tb00482.x
|View full text |Cite
|
Sign up to set email alerts
|

Luminol‐Enhanced Chemiluminescent Response of Human Melanocytes and Melanoma Cells to Hydrogen Peroxide Stress

Abstract: The response of human melanocytes and melanoma cells to hydrogen peroxide stress was measured. Cells were exposed to glucose/glucose oxidase or free H2O2 and reactive oxygen species measured by luminol‐enhanced chemiluminescence. The response was distinctly different between the two types and the addition of superoxide dismutase to melanoma cells paradoxically enhanced the chemiluminescent signal. These findings coupled with other known differences between the way these two types of cells handle oxidative stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 9 publications
0
42
0
1
Order By: Relevance
“…In contrast, the relative amount of hydrogen peroxide in melanoma cells decreased with time while intracellular superoxide anion in melanoma cells seemed to accumulate and was 3-to 4-fold that of normal melanocytes (Table 1). We have demonstrated elsewhere that melanoma cells quench an exogenous peroxidative stress poorly and, in fact, paradoxically generate a pro-oxidant response to oxidant stress, most likely mediated by superoxide anion [16]. This oxidant stress was resisted by melanocytes and no apoptosis occurred while apoptosis was markedly increased in melanoma cells.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In contrast, the relative amount of hydrogen peroxide in melanoma cells decreased with time while intracellular superoxide anion in melanoma cells seemed to accumulate and was 3-to 4-fold that of normal melanocytes (Table 1). We have demonstrated elsewhere that melanoma cells quench an exogenous peroxidative stress poorly and, in fact, paradoxically generate a pro-oxidant response to oxidant stress, most likely mediated by superoxide anion [16]. This oxidant stress was resisted by melanocytes and no apoptosis occurred while apoptosis was markedly increased in melanoma cells.…”
Section: Discussionmentioning
confidence: 92%
“…This finding is surprising in that most tumor cells exhibit an antioxidant phenotype [14,15]. We have also previously shown that melanocytes and melanoma cells respond differentially to exogenous peroxide with melanocytes efficiently suppressing this stress and melanoma cells unable to do so [16]; surprisingly, melanoma cells were not just unable to suppress a peroxide stress, but generated a pro-oxidant response.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…(Meyskens et al 1997). The conclusions from our studies are summarized as follows, and illustrated in Fig.…”
Section: Redox Status Of Melanocytes and Melanoma Cellsmentioning
confidence: 99%
“…Certain ROS scavengers and inhibitors of ROS generation inhibit UV-induced melanogenesis and antioxidants like reduced glutathione (GSH) and ascorbic derivatives are applied to treat various skin problems such as depigmentation of hyperpigmented spots [5,6]. Hence, antioxidants and free radical scavengers also play an important role in protecting human skin from the harmful effects by UV radiation as hyperpigmentation [7].…”
Section: Introductionmentioning
confidence: 99%